MENINGKATKAN KETERAMPILAN SERVIS DAN PASSING BOLA VOLI MELALUI PERMAINAN VOLSAL PADA SISWA KELAS III SD KATOLIK 143 BHAKTYARSATAHUN PELAJARAN 2017/2018 - Frederiksen Novenrius S. Timba (Jurnal Akrab Juara, 2019)
The researcher has got the data of research result from each cycle which shows the improvement of the students skill. On the observation of the teacher activity in first cycle of Meeting one reached an average of 76.31 and Meeting two reached an average of 81.57as a good categories. In the second Cycle of Meeting one reached an average of 89.47 and Meeting two to 96.05 with very good category. In the first cycle of student activity in Meeting one reached 80 average with a good category, and Meeting two reached 85 category averageas a very well category. While in the second cycle of Meeting one reached an average of 90 as very well categories and Meeting two increased again to 95 with very good category. On the observation result of student attitude in learning process at first cycle of meeting one reaching average 84,28 with good category, in meeting 2 reaching average 88,57 with very good category, while at second cycle of meeting one reach flat 92, 85 with very good category, and meeting 2 reaches average 95,71 with very good category. On the skills of students who experienced an increase in the first cycle of meeting one the average score reached 79.46 students and meeting 2 students average score reached 83.92 and 100% classical completeness with good category. The average value obtained in second cycle of meeting one is 92.41 and the meeting two is 97.32 and the classical completeness is 100% in very good category. Thus it can be concluded that the use of volsal game can improve the students' skills of the service materials and volleyball that passes on the third grade students of Catholic Elementary School 143 Bhaktyarsa of Sikka Regency in the Academic Year of 2017/2018.